Body and testicular traits, libido testing and semen analysis of young males from the Blanco Orejinegro (Bos taurus) herd of University of Antioquia, throughout puberty onset - Urrea, German; Cordoba, Sandra L.; Neira, Jorge A.; Maldonado Estrada, Juan Guillermo (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary Fifteen young males (mixed ages) from the BON herd of University of Antioquia were selected and followed weekly from August to December 1998 (Comprising a range from 9,9 to 28,1 months, from 19 time points of data collection) in order to measure and evaluate: 1) Body and Testicular traits (n=322); 2) Libido testing (LibT, n=19); 3) Response to rectal palpation of seminal vesicles reflex (SVR, n=244); and 4) Analysis of semen collected by artificial vagina (n=42). Data of physical traits were categorized monthly from 10 to 27 months (n=17 groups); and data of semen were categorized into three groups (16,1 to 21; 21,1 to 24; and 24,1 to 27 months). Simple regression analysis was performed between each trait (dependent variable) and age (independent variable). Multivariate analysis of variance was used to establish differences between groups and monthly reference values for each trait. Physical traits proportionally increased (p < 0,01) with age: Body Weight (R2=0,796) and Scrotal Circumference (R2=0,672), had the highest correlation coefficients, whereas Body Length (R2=0,454), Withers height (R2=0,506), Testis Diameter (R2=0,415), and Testis Length (R2=0,458), had a mild correlation. Higher scores for LibT (more than 5 mating attempts/5 minutes) were always observed. Individual responses to SVR (secretion of pre-seminal fluid, protrusion of penis and complete erection) proportionally increased with age (R2=0,539; p < 0,01). The youngest age at semen collection was 16,1 months (1,63 x 108 sperm/cc, with > 60% gross and individual progressive motility); however, no correlation was found with age, neither for volume (3,6 ml), nor for pH (6,86) or semen concentration. These results suggest the onset of puberty occurs between 13 and 14 months for this BON herd and confirm previous observations on the high libido of BON males. Reference values are reported for both testicular and body traits. Breeding Soundness Examination rather than merely semen concentration must be considered in order to define the onset of puberty in bovine cattle. Key words: bovine, criollo cattle, puberty, semen, tropical environment, young bulls. Resumen Quince toretes (de diferentes edades) del hato BON de la Universidad de Antioquia fueron evaluados cada semana, desde agosto hasta diciembre de 1998 (incluyendo un rango de edad de 9,9 a 28,1 meses, en 19 fechas de medición), para evaluar: 1) Medidas corporales y testiculares; 2) Prueba de la líbido (LibT); 3) Reflejo a la palpación de las vesículas seminales (SVR, n=244) por masaje rectal; y 4) Análisis de muestras de semen (n=42) obtenidas mediante vagina artificial. Los datos de medidas corporales y testiculares fueron categorizados en grupos de un mes (desde 10 hasta 27 meses; n=17 grupos); y para el análisis del semen se categorizaron en tres grupos (16,1 a 21, 21,1 a 24, y 24,1 a 27 meses). Pruebas de regresión simple se hicieron incluyendo cada parámetro como variable dependiente y la edad como variable independiente. La prueba de ANOVA Multifactorial se utilizó para definir diferencias y valores de referencia para cada parámetro. Las medidas corporales y testiculares aumentaron proporcionalmente con la edad (p < 0,01): el peso corporal (R2=0,796) y la circunferencia escrotal (R2=0,672) mostraron la más alta correlación con la edad, mientras que mostraron una mediana correlación la longitud corporal (R2=0,454), la alzada (R2=0,506), el diámetro del testículo (R2=0,415), y la longitud del testículo (R2=0,458). En la LibT, la mayoría de los toretes mostraron más de cinco intentos de monta/5 minutos. La intensidad de la respuesta individual al masaje rectal (secreción de líquido preseminal, protrusión del pene y erección completa), aumentó proporcionalmente con la edad (R2=0,539; p < 0,01). El primer eyaculado se recolectó a la edad de 16,1 meses (1,63 x 108 espermatozoides/cc, con mas de 60% de movilidad progresiva en masa e individual); sin embargo, no se halló correlación entre el volumen (3,6 ml), el pH (6,86), o la concentración del semen, con la edad. Los resultados sugieren un inicio de la pubertad entre 13 y 14 meses de edad para el grupo de toretes de este hato. Ademas, se informan los valores de referencia para cada medida corporal y testicular, en el rango de edad evaluado. Palabras clave: bovinos, ganado criollo, pubertad, semen, toretes, trópico.